PENGARUH MEDIA VIDEO ANIMANSI POWTOON BERBASIS KEARIFAN LOKAL TERHADAP HASIL BELAJARAN IPAS KELAS IV SEKOLAH DASAR - Smita Manurung, Elida; Aryaningrum, Kiki; Sunedi, Sunedi (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
This study aims to determine the Effect of Local Wisdom-Based Powtoon Animation Video Media on the Learning Outcomes of Grade IV Elementary School Science. The results of observations and interviews with grade IV teachers at Elementary School 117 Palembang found that the level of learning outcomes of students in Natural and Social Sciences (IPAS) had not developed well, students were less motivated during the teaching and learning process. The researcher used an experimental method, a post-test only control group design. Design. Samples of grade 4D and 4E students at Elementary School 117 Palembang. Data collection techniques were observation, testing and documentation. The analysis technique used data normality test, data homogeneity test and hypothesis test of the effect of Local Wisdom Powtoon Animation Video Media on the Learning Outcomes of Grade IV Elementary School Science. This can be concluded from the learning outcomes in the control class posttest score of 55.66 and in the experimental class of 84.48 from both classes, it can be seen that the class that received the treatment had better learning outcomes for the experimental class compared to the control class, the score increased. From the normality test data, it was obtained 0.108 for the control class and 0.128 for the experimental class, it can be seen that the learning outcomes of children in the control and experimental classes were greater than 0.05, so the data was normally distributed. The results of the homogeneity test obtained a significant value of 0.973> 0.05, so the control and experimental classes were called homogeneity. Conduct a hypothesis test from the data that has been obtained using the independent simple t-test. In the data obtained, the significant value (2-tailed) is 0.000 <0.05, so Ho is rejected and Ha is accepted. After conducting the test, the researcher concluded that there was a significant influence on the Local Wisdom-Based Powtoon Animation Video Media on the Learning Outcomes of Science in Grade IV Elementary Schools. ABSTRAKPenelitian ini bertujuan untuk mengetahui Pengaruh Media Video Animasi Powtoon Berbasis Kearifan Lokal Terhadap Hasil Belajar IPAS Kelas IV SD. hasil observasi dan wawancara dengan guru kelas IV di SD Negeri 117 Palembang ditemukan bahwa tingkat hasil belajar Ilmu Pengetahuan Alam dan Sosial (IPAS) siswa belum berkembang dengan baik, siswa kurang termotivasi selama proses kegiatan belajar mengajar berlangsung. Peneliti menggunakan metode eksperimen jenis post-test only control grup design. Design. Sampel siswa kelas 4D dan 4E SD Negeri 117 Palembang. Teknik pengumpulan data observasi, tes dan dokumentasi. Teknik analisis menggunakan uji normalitas data, uji homigenitas data dan uji hipotesis pengaruh Media Video Animasi Powtoon Kearifan Lokal Terhadap Hasil Belajar IPAS Kelas IV Sekolah Dasar. Hal ini dapat disimpulkan dari hasil belajar pada nilai posttest kelas kontrol yaitu 55,66 dan pada kelas eksperimen yaitu 84,48 dari kedua kelas ini terlihat kelas yang mendapatkan perlakuan nilai hasil belajar anak kelas eksperimen lebih baik dibandingkan kelas kontrol skor meningkat. Darai data uji normalitasnya diperoleh 0,108 untuk kelas kontrol dan 0,128 untuk kelas Eksperimen terlihat hasil belajar anak pada kelas kontrol dan eksperimen lebih besar dari 0.05 maka data berdistribusi normal. Hasil uji homogenitas diperoleh nilai signifikan sebesar 0,973 > 0,05 maka kelas kontrol dan eksprimen disebut homogenitas. melakukan uji hipotesis dari data yang sudah diperolehlah mempergunakan uji independent simple t-test. Pada data yang diperolehlah nilai signifikan (2-tailed) adalah 0,000<0,05, maka  ditolak dan diterima data tersebut. Setelah melakukan pengujian peneliti menyimpulkan bahwa terdapatnya pengaruh yang signifikan terhadap Media Video Animasi Powtoon Berbasis Kearifan Lokal Terhadap Hasil Belajar IPAS Kelas IV Sekolah Dasar.